Optimizing Legal Protection for Agricultural Products as Intellectual Property Assets (Study in Central Java) - Kusumaningrum, Rindia Fanny (Law Research Review Quarterly, 2015)
Indonesia as a member of the World Trade Organization and supporter of the idea of the ASEAN Free Trade Area has shown that the Indonesian Government strongly supports a free and open economic system. The logical consequence of Indonesia as a WTO member in accordance with the principle of pacta sunt servanda must be to obey TRIP's international agreement as an agreement with WTO members in accordance with Law No. 7 of 1994 concerning Ratification of the Agreement Establishing the World Trade Organization. Free trade that continues to increase requires Indonesia to compete with other ASEAN countries in various sectors. Indonesia as an agricultural country, for its agricultural products is diverse and very abundant, agricultural products in Central Java are no exception. Keywords: Agricultural Products, Intellectual Property, Legal Protection